The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
48th AIAA/ASME/ASCE/AHS/ASC Structures, Structural Dynamics, and Materials Conference 2007
DOI: 10.2514/6.2007-1898
|View full text |Cite
|
Sign up to set email alerts
|

Application of a Weighted Average Surrogate Approach to Helicopter Rotor Blade Vibration Reduction

Abstract: The advantages of employing multiple approximation methods and the effectiveness of weighted average surrogate modeling for approximation and reduction of helicopter vibrations is studied. Multiple surrogates, including the weighted average approach, are considered so that the need to identify the "best" approximation method for the rotor vibration reduction problem is eliminated. Various approximation methods are used to generate a vibration objective function corresponding to a flight condition in which blad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…First, for the kth sub-domain, construct multiple different candidate surrogates, and calculate the corresponding GMSE based on leave-one-out cross-validation by (15) of each surrogate as the criterion to measure its accuracy. Then the sequence of the surrogates according to GMSE in the ascending order can be obtained, and denote the candidate model set with the ranking sequence as M k so as to compose a more accurate ensemble, the first issue is to define the number of contributing surrogates n k * M ≤ n M to be selected.…”
Section: Surrogate Ensemble Modeling For Sctv Predictionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, for the kth sub-domain, construct multiple different candidate surrogates, and calculate the corresponding GMSE based on leave-one-out cross-validation by (15) of each surrogate as the criterion to measure its accuracy. Then the sequence of the surrogates according to GMSE in the ascending order can be obtained, and denote the candidate model set with the ranking sequence as M k so as to compose a more accurate ensemble, the first issue is to define the number of contributing surrogates n k * M ≤ n M to be selected.…”
Section: Surrogate Ensemble Modeling For Sctv Predictionmentioning
confidence: 99%
“…One popular ensemble method is using the weighted sum approach [14]. Goel et al [15] study the effectiveness of the weighted aggregation method for the approximation of helicopter vibrations. Wang et al [16] employ the weighted average surrogate to solve the problem of computationally expensive function evaluations in optimization.…”
Section: Introductionmentioning
confidence: 99%
“…They showed that due to small islands in the design space where mixing is very effective compared to the rest of the design space, it is difficult to use a single surrogate model to capture such local but critical features. Glaz et al 135 used polynomial response surfaces, kriging, radial basis neural networks, and weighted average surrogate for helicopter rotor blade vibration reduction. Their results indicated that multiple surrogates can be used to locate low vibration designs which would be overlooked if only a single approximation method was employed.…”
Section: Multiple Surrogates and Metamodel Ensemblesmentioning
confidence: 99%
“…This idea has been explored in the past, for example, by Mack et al [55], by using a combination of polynomial respose surface methods and radial basis functions, for performing global sensitivity analysis and shape optimization of bluff bodies. Also, Glaz et al [28] adopted three approximation models, namely polynomial, kriging, and radial basis functions. This combined approach, adopted a weighted estimation from the different models, which was used to reduce the vibration for a helicopter rotor blade.…”
Section: Conclusion and Future Research Pathsmentioning
confidence: 99%